PENGARUH PENEMPATAN KERJA DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PT. ANGKASA PURA SOLUSI DI BANDAR UDARA INTERNASIONAL KUALANAMU - Putri Tiara Devi; Lukman Nasution (LPPM Universitas Labuhanbatu, 2021)
The quality and quantity of work achieved by an employee in carrying out his duties under the responsibilities given to him are referred to as performance. Many factors affect performance including work placement and competence. To determine the effect of work placement and competence on the performance of employees of PT. Angkasa Pura Solusi at Kualanamu International Airport partially or simultaneously is the purpose of this research. This type of research is a quantitative descriptive method. The object of research in this study were employees of the Aviation Security Division of PT. Angkasa Pura Solusi totaling 336 people. A sample of 183 people was obtained using the Slovin formula. Multiple regression analysis, partial test, simultaneous test, and determination test were used as data analysis tools. The results of this study are partially and simultaneously work placement and competence affect employee performance. In terms of job placement, it should be based on academic achievement and employee experience. Determining these criteria, the company needs to get employees who fit the job description. To competence, the company is advised to select and prepare prospective workers who have advantages in the form of knowledge, specific skills, potential, talent values that are per the character and goals of the company